The State of U.S. Urban Water: Data and the Energy‐Water Nexus - Chini, Christopher M.; Stillwell, Ashlynn S. (Water resources research, 2018)
Data on urban water resources are scarce, despite a majority of the U.S. population residing in urban environments. Further, information on the energy required to facilitate the treatment, distribution, and collection of urban water are even more limited. In this study, we evaluate the energy‐for‐water component of the energy‐water nexus by providing and analyzing a unique primary database consisting of drinking water and wastewater utility flows and energy. These anthropogenic fluxes of water through the urban environment are used to assess the state of the U.S. urban energy‐water nexus at over 160 utilities. The average daily per person water flux is estimated at 560 L of drinking water and 500 L of wastewater. Drinking water and wastewater utilities require 340 kWh/1,000 m3 and 430 kWh/1,000 m3 of energy, respectively, to treat these resources. The total national energy demand for water utilities accounts for 1.0% of the total annual electricity consumption of the United States. Additionally, the water and embedded energy loss associated with non‐revenue water accounts for 9.1 × 109 m3 of water and 3,100 GWh, enough electricity to power 300,000 U.S. households annually. Finally, the water flux and embedded energy fluctuated monthly in many cities. As the nation's water resources become increasingly scarce and unpredictable, it is essential to have a set of empirical data for continuous evaluation and updates on the state of the U.S. urban energy‐water nexus. Plain Language Summary Energy in the form of electricity, natural gas, or fuel oil is needed to treat and distribute drinking water to consumers in cities. Additional energy is needed after using drinking water to collect and treat subsequent wastewater. Though most of the U.S. population lives in urban areas, there are no studies that collect and publish data from across U.S. cities to determine how much water is used or how much energy is used for that water. In this study, we collect data from over 160 drinking water or wastewater utilities in U.S. cities to determine water demands and their required energy. Through our study, we determined that almost 1 of every 6 units of water treated across the United States never reaches the consumer. The energy required to treat this lost water is enough to power 300,000 homes in the United States annually. Through this collection of data, we provide the first freely available database for further research and understanding of city‐level water flows. Cataloging these data across the United States is important for conserving water and energy resources and promoting sustainable practices. Key Points We present a database of primary flow and energy data for over 160 U.S. water and wastewater utilities Average per person water flux is 560 L of drinking water and 500 L of wastewater per day Non‐revenue water and its embedded energy accounts for 3,600 GWh of electricity loss annually